2019
DOI: 10.5216/ree.v21.52253
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento da equipe de enfermagem sobre ressuscitação cardiopulmonar em um hospital universitário

Abstract: Objetivou-se identificar o conhecimento teórico da equipe de enfermagem sobre as manobras de ressuscitação cardiopulmonar em suporte básico de vida, associando tal conhecimento às variáveis sociodemográficas, econômicas e de formação profissional. Trata-se de estudo transversal, descritivo e quantitativo, cujos dados foram obtidos de questionários aplicados a 351 funcionários de uma equipe de enfermagem de um serviço de emergência e de unidades de terapia intensiva. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
0
4
1
10
Order By: Relevance
“…The results of the theoretical and practical evaluation before T1 showed that both groups had a low level of theoretical and practical knowledge in CPR. These data differ from the study that evaluated the knowledge of the nursing team in BLS and showed that the highest rates of hits were related to the highest level of education, specialization in critical areas, time of experience below ve years and previous training in ACLS, while the lowest rates of hits were associated with work in non-critical areas [12].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of the theoretical and practical evaluation before T1 showed that both groups had a low level of theoretical and practical knowledge in CPR. These data differ from the study that evaluated the knowledge of the nursing team in BLS and showed that the highest rates of hits were related to the highest level of education, specialization in critical areas, time of experience below ve years and previous training in ACLS, while the lowest rates of hits were associated with work in non-critical areas [12].…”
Section: Discussioncontrasting
confidence: 99%
“…For the practice, the T2 had the same effect in both and the scores were the same observed in T1, showing that the retraining improved the knowledge, especially that of the CCU group. Any previous training is associated with better CPR skills, as it helps in learning and xing the contents [12,23]. Another study indicated a positive association between the performance of participants in CPR, the frequency of training and whether CPR training was offered in the workplace [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A partir daí, sucederam diversas internações hospitalares, juntamente com acompanhamento presencial compartilhado por equipes da Unidade Básica de Saúde (UBS) e CAPS II ao qual ele era vinculado. Em 2019, começou a apresentar recidiva dos sintomas, acompanhado de isolamento domiciliar, ausência de higiene e recusa alimentar, sensibilizado a retomar o acompanhamento presencial na UBS à qual equipe o acompanhava. Em 16 de abril de 2020, o CAPS II foi informado por familiar do paciente que o mesmo "havia ateado fogo à própria cabeça", sendo encaminhado ao hospital e recebendo cuidados até o dia da alta, 25 de abril de 2020.…”
Section: Relato De Casounclassified
“…Nesse cenário, os cuidados pós-PCR realizados pela equipe de enfermagem, substanciais à progressão clínica do paciente, englobam a monitorização hemodinâmica, a realização de exames laboratoriais e cuidados específicos. A equipe deve deter o conhecimento técnico-científico necessário acerca da fisiopatologia da SPPC e das medidas terapêuticas mais adequadas a serem praticadas (Guskuma et al, 2019).…”
Section: Introductionunclassified